Pengaruh Kecerdasan Emosional dan Sikap Siswa terhadap Pemahaman Konsep Kimia - Theresia Evy Yulianty Nadeak (Universitas Indraprasta PGRI Jakarta, 2020)
A positive attitude towards a subject will lead students to full attention to studying it. On the other hand, a negative attitude will take the students away from the subject which in turn affects the level of student’s ability to understand concepts, especially in chemistry. The purpose of this study is to determine whether there are effects of emotional intelligence and students’ attitude towards students' understanding of chemical concepts, especially in public Senior High School in South Jakarta. This research occupied a quantitative method using survey and multiple regression analysis techniques. Data collection was conducted by distributing questionnaires for emotional intelligence and student attitude, and multiple-choice items test for understanding chemical concepts. The population of this study was Grade X of Public Senior High School in South Jakarta, Academic Year 2018/2019, amounting to 858 students with a sample of 90 students. The results of this study concluded that 1) There is a significant influence of emotional intelligence together with attitudes of students on understanding the chemical concept of public senior high school students in South Jakarta with a contribution of 52.2%. 2) There was a significant effect of emotional intelligence on the understanding of chemical concepts with a contribution of 24.6%, 3) There was a significant effect of students attitudes on the understanding of chemical concepts with a contribution of 9.69%.